The Reconceptualization Movement in Latin America: : Argentina, Chile and Colombia - Quintero-Londoño, Sergio Andrés (2025)
Based on the results of the network research entitled “The Reconceptualization Movement of Social Work in Latin America: Historical Determinants, International Interlocutions and Memory (1960-1980)”; whose objective is to analyze the processes of constitution of the critical strands of Social Work in Latin America, between the 1960s and 1980s in the context of monopoly capitalism, the points of articulation between the experiences of Argentina, Chile and Colombia in the so-called Reconceptualization Movement are presented. First, we will present the international context in which the Reconceptualization Movement emerged and its main theoretical-political influences. Secondly, we will review the particularities of each country, to finally present the collective synthesis of the analysis work carried out.